2018
DOI: 10.1186/s12885-017-3966-1
|View full text |Cite
|
Sign up to set email alerts
|

The quality of working life questionnaire for cancer survivors (QWLQ-CS): factorial structure, internal consistency, construct validity and reproducibility

Abstract: BackgroundTo assess the factorial structure, internal consistency, construct validity and reproducibility of the Quality of Working Life Questionnaire for Cancer Survivors (QWLQ-CS).MethodsAn Exploratory Factor Analysis (EFA) was performed on QWLQ-CS data from a sample of employed cancer survivors to establish the final number of items and factorial structure of the QWLQ-CS. Internal consistency was assessed using Cronbach’s alpha. In a second sample of (self-)employed cancer survivors, construct validity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
0
32
1
Order By: Relevance
“…Interpretability was assessed by comparing the SDC with the MIC at three levels: (a) for the QWLQ‐CS total score and each subscale individually, (b) for use at group and individual level separately, and (c) for improvement and deterioration separately. SDC_ind was derived from the Standard Error of Measurement (SEM_agreement) (de Jong et al, ) using the following formula: (1.96 * √2 * SEM_agreement) (de Vet et al, ) and for use at group level SDC_group = SDC_ind/√(N) (de Vet et al, ). The MIC for improvement and deterioration was based on the mean change method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpretability was assessed by comparing the SDC with the MIC at three levels: (a) for the QWLQ‐CS total score and each subscale individually, (b) for use at group and individual level separately, and (c) for improvement and deterioration separately. SDC_ind was derived from the Standard Error of Measurement (SEM_agreement) (de Jong et al, ) using the following formula: (1.96 * √2 * SEM_agreement) (de Vet et al, ) and for use at group level SDC_group = SDC_ind/√(N) (de Vet et al, ). The MIC for improvement and deterioration was based on the mean change method.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of working life of cancer survivors can be measured with the Quality of Working Life Questionnaire for Cancer Survivors (QWLQ‐CS) (de Jong, Tamminga, van Es, Frings‐Dresen, & de Boer, ), which is a patient‐reported outcome measurement (PROM) that contains 23 items divided into five subscales (de Jong et al, ). A previous study has shown good internal consistency, construct validity, and reproducibility of the QWLQ‐CS (de Jong et al, ). However, to be able to use the QWLQ‐CS as a PROM of an intervention in research or practice, the responsiveness and interpretability of the QWLQ‐CS need to be determined (Mokkink, Terwee, Patrick, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarities between both questionnaires relate to the measured constructs, i.e. 'quality of working life' and 'successfulness of return to work', and in the recall period of 4 weeks [22]. Differences relate to their usability for self-employed cancer survivors, which applies to the QWLQ-CS [22], but not for the I-RTW_CS, and in the weighting of the items based on their perceived importance for the individual cancer survivor, which only applies to the I-RTW_CS.…”
Section: Interpretation Of Findingsmentioning
confidence: 97%
“…The answer option 'does not apply' for self-employed cancer survivors was omitted, as they were not included in this study. The QWLQ-CS has sufficient to good measurement properties in cancer survivors [22].…”
Section: Variables and Measuresmentioning
confidence: 99%